Developing Augmented Reality-Integrated Worksheets for Teaching Descriptive Writing in Junior High School - Farah Assyfa Gayo; Siska Rizkiani; Yana (IKIP Siliwangi, 2026)
Augmented Reality (AR) is one of the technologies used in education. With its advanced features, AR can support innovative instruction. The use of AR in descriptive text writing instruction is still understudied. Therefore, the present study aims to investigate the process, the feasibility, and students’ responses to the use of AR-integrated descriptive text worksheets in teaching writing in junior high school. This study employed Research and Development (R&D) methods with an ADDIE model, comprising five stages: Analysis, Design, Development, Implementation, and Evaluation. Thirty-two seventh-grade students at MTsN Kota Cimahi were the subjects of this study. Validation sheets and questionnaires were used to obtain the research data, and descriptive analysis was used as the data analysis technique. The findings revealed that the development of AR-integrated descriptive text worksheets is suitable to be used in writing instruction at the junior high school. The feasibility of the developed descriptive text worksheet obtained a percentage of 83,3% in the valid category. Last, students’ responses of AR-based worksheets showed positive outcomes. It can be concluded that AR-integrated descriptive text worksheet for teaching writing in junior high school is feasible and appropriate to support innovative and engaging writing instruction.